Comparing the physical activity patterns of 3-year-old Finnish and Australian children during childcare and homecare days - Soini Anne; Watt Anthony; Tammelin Tuija; Soini Markus; Sääkslahti Arja; Poskiparta Marita (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2014)
Background: Limited previous research has contrasted physical activity (PA) patterns in preschool children across different hourly patterns or segments of day, or adopted similar methodologies to compare the PA behaviors of children from different countries. The purpose of this study was to examine how the PA levels and patterns differed between 3- year-olds within and between childcare and homecare days in Finland and Australia.